PENGARUH ROLE STRESS, ROLE AMBIGUITY DAN WORK FAMILY CONFLICT TERHADAP KOMITMEN ORGANISASIONAL KARYAWAN - Geria Utama, I Nyoman; Ayu Sriathi, Anak Agung (E-Jurnal Manajemen, 2016)
Bali is a tourist area, where many industries are growing restaurant industry is no exception, so many workers absorbed, for it manjaga the company's survival and sustainable, restaurant or other industries must have the resources to compete. This research was conducted at The Sardine Restaurant in Seminyak Kerobokan Bali. Method of determination of the samples used in research in this tian is a census method, and the number of Samel gained as much as 56 respondents. The analysis technique used in this research is multiple linear analysis techniques. This study shows results that role stress have a significant negative effect on organizational commitment, role ambiguity have a significant negative effect on organizational commitment and work family conflict has significant negative influence on organizational commitment .
Keywords: role stress, role ambiguity, work family conflict and organizational commitment